[Martin riding his bike] - Rafael Antolino::::::photographer::: (2005)
Description supplied by photographer: 'Mi hermanito Martin, andando en su Bicicleta afuera de nuestra casa en Paso Robles. El tiene 9 años y aparte de que nos gusta la misma música tambien jugamos a la lucha libre.' Translation of description: 'My little brother Martin is riding his bike outside our house in Paso Robles. He is 9 years old and he likes the same music I like. We play around and wrestle.'